2011
DOI: 10.1055/s-0031-1296309
|View full text |Cite
|
Sign up to set email alerts
|

Comparative bioavailability of betahistine tablet formulations administered in healthy subjects

Abstract: Since the 90% CI for Cmax and AUCs ratios were all within the 80-125% interval proposed by the US Food and Drug Administration Agency, it was concluded that the test formulation is bioequivalent to the reference for both the rate and the extent of absorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…To be able to compare animal studies with clinical studies using oral administration, we calculated the plasma concentration of betahistine achieved by intravenous injection of guinea pigs and designed the present study according to the results. The data presented here taken together with the pharmacokinetic of betahistine in human test persons [24], [25] leads to the conclusion that a further increase in cochlear perfusion in patients suffering from Menière’s disease might be achieved by doses higher than currently applied. While this calculation allows only a very rough estimation of plasma concentrations, we believe that it is much more instructive than directly comparing dosage administered via oral intake versus intravenous administration as in earlier experimental concepts.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…To be able to compare animal studies with clinical studies using oral administration, we calculated the plasma concentration of betahistine achieved by intravenous injection of guinea pigs and designed the present study according to the results. The data presented here taken together with the pharmacokinetic of betahistine in human test persons [24], [25] leads to the conclusion that a further increase in cochlear perfusion in patients suffering from Menière’s disease might be achieved by doses higher than currently applied. While this calculation allows only a very rough estimation of plasma concentrations, we believe that it is much more instructive than directly comparing dosage administered via oral intake versus intravenous administration as in earlier experimental concepts.…”
Section: Discussionmentioning
confidence: 81%
“…Two clinical trials support our view; they found that the dosages of 48 mg tid are more effective than 16 or 24 mg tid [13] and even higher dosages of 160 mg tid [14] are even more effective. Additionally, time T max from oral administration to peak concentration has been shown to be 0.79 h (SD: 0.32 h) to 0.98 (SD: 0.47) in healthy volunteers [24], [25]. Assuming that Menière’s disease can be treated by betahistine through increasing cochlear perfusion and thereby reducing a causative endolymphatic hydrops, we conclude that either high doses of up to 160 mg tid or more frequent administration of betahistine could be advantageous for patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the end product of betahistine metabolism is pyridylacetic acid, an inactive compound that can be found in both urine and plasma after oral betahistine ingestion (Chen et al, 2003;Val et al, 2010). Hypothesized degradation paths give rise to the metabolites aminoethylpyridine and hydroxyethylpyridine (Bowman et al, 1972;Sternson et al, 1974;Chen et al, 2003;Val et al, 2010). These metabolites have been shown to possess an affi nity to histamine-receptors on their own (Fossati et al, 2001).…”
Section: Anova Analysis Of Variancementioning
confidence: 99%
“…There are few bioanalytical reports available for the quantitation of betahistine using 2PAA as the key surrogate in human plasma (Chen et al ., ; Moorthy et al ., ; Val, Chen, Mendes, & De Nucci, ). The method of Chen et al .…”
Section: Introductionmentioning
confidence: 99%